Narrow host range phages associated with citrus canker lesions in Florida and Argentina - Balogh, B. (2013)
Bacteriophages were isolated from naturally infected citrus canker lesions from diverse locations in Florida and Argentina and characterized for host range using a world-wide collection of Xanthomonas citri subsp. citri (Xcc) strains. Sixty-seven bacteriophages isolated from citrus canker lesions in Florida (37 bacteriophages) and Argentina (30 bacteriophages) revealed little diversity. All 30 phages isolated from four locations in Argentina had identical host ranges (group ARG), while 37 phages from Florida made up two groups (FLA and FLB). ARG and the 31 FLA phages produced clear plaques and had nearly identical host ranges as phage CP2 of Japan in that they only reacted with typical A strains and none of the atypical A strains (A* and AW) or other Xanthomonas spp. FLB phages had a different host range from the other strains and produced turbid plaques. We used phage typing, fatty acid analysis and riboprinter analysis to classify citrus-associated xanthomonads. Phage typing using 12 phages isolated from Xcc, X. fuscans subsp. aurantifolii (Xfa), X. alfalfae subsp. citrumelonis (Xacm), and other sources proved useful for classifying all major Xcc pathotypes and/or strains (A, A*, Miami (MI), Manatee (MA) and Wellington (AW)), as well as B and C types of Xfa. X. citri subsp. citri strains from a worldwide collection were diverse in phage susceptibility. The majority of Xcc strains, which originated from different regions of the world and which were typical “A” pathotype strains based on pathogenicity characteristics, was sensitive to most phages (including CP2, FLA and ARG), and had nearly identical phage sensitivity profiles. MA strains were quite unique in that they reacted with none of the phages; furthermore, they were different from the putative progenitor MA strain, ATCC 49118, which reacted with a group of phages. Fatty acid analysis revealed considerable variation in Xcc-A, Xfa-B, Xfa-C and Xacm strains. Using riboprinter analysis, we identified a unique riboprinter pattern for strains isolated from an etrog tree (Citrus medica) in Florida that were “A” pathotype strains based on pathogenicity characteristics. Phage typing and fatty acid analysis were useful in corroborating that the etrog strains represent a unique new Xcc strain in Florida.